Review of Cipher Text Update and Computation Outsourcing in Fog Computing For Internet of Things. - Vali, Shaik Jaffer; Sheetlani, Jitendra (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Fog computing is a worldview that stretches out distributed computing to the edge of the network. It can give calculation and capacity administrations to end gadgets in Internet of Things (IoT). Property based cryptography is a notable innovation to ensure data classification and fine-grained data access control. Notwithstanding, its computational expense in encryption and decoding stage is straight with the intricacy of strategy. In this paper, we propose a safe and fine-grained data access control conspire with ciphertext update and calculation redistributing in fog computing for IoT. The delicate data of data proprietor are first encoded utilizing trait based encryption with numerous arrangements and afterward moved operations to distributed storage. Consequently, the user whose ascribes fulfill the entrance strategy can decode the ciphertext. In view of property based mark method, approved user whose credits coordinated in the mark fulfill the update strategy can recharge the ciphertext. In particular, a large portion of encryption, decoding and marking calculations are re-appropriated from end gadgets to fog hubs, accordingly the calculations for data proprietors to scramble, end users to unscramble, re-encode and sign are unessential to the quantity of characteristics in the strategies.